Experiences in IETF-BMWG: Towards a Methodology for VNF Benchmarking Automation - Rosa, Raphael; Rothenberg, Christian (Anais do Workshop Pré-IETF (WPIETF); 2020: Anais do VII Workshop Pré-IETFDO - 10.5753/wpietf.2020.13795, 2020)
Network Functions Virtualization (NFV) aims at high-end carriergrade performance but lacks common methodologies for testing Virtual Network Functions (VNFs). Benchmarking VNFs should consider different degrees of freedom instead of the black-box common approaches created for bare metal network functions. We understand such status-quo needs to be altered having basis on the solid ground of extensive and automated experimentation. Since 2015, we have been addressing a role in this scenario, from a position paper to the creation of the draft “Methodology for VNF Benchmarking Automation” in the Internet Engineering Task Force (IETF) Benchmarking Methodology Working Group (BMWG). This paper tells the tale about this draft in BMWG, associated with the perks of developing an open source reference implementation and academic papers, as the means of the old IETF mantra on running code. The story intends to showcase our experiences in IETF and BMWG, covering technical content (e.g., YANG models) as much as draft reviews on mailing-lists.